Prevalence of Anemia and Its Associated Factors in Antiretroviral-Treated HIV/AIDS-Positive Adults from 2013 to 2018 at Debre Berhan Referral Hospital, Ethiopia. (11th March 2020) - Aynalem, Yared Asmare; Shibabaw Shiferaw, Wondimeneh; Woldiye, Zeleke
Abstract : Introduction . Anemia was defined as a hemoglobin level of less than or equal to 13.9 g/dl for male and less than or equal to 12.2 g/dl for female adults. It is one of the most common hematological abnormalities in people living with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) and is a determining factor for disease progression and death. Among the countries in sub-Saharan Africa, Ethiopia is one of the most affected nations by HIV. Therefore, this study aimed to assess the prevalence of anemia and its associated factors among HIV-positive adults that had received antiretroviral treatment (ART) at Debre Berhan Referral Hospital. Methods . An institution-based, descriptive, cross-sectional study was conducted involving 263 adults with HIV/AIDS that had undergone ART at Debre Berhan Referral Hospital, Ethiopia. Data were collected from patient charts using systematic sampling with a pretested data extraction tool and entered using EpiData 3.1. Variables having a p value ≤0.25 in the bivariate were fitted to a multivariable regression model with a 95% confidence interval. p values ≤0.05 were considered statistically significant in the multivariate analysis. Results . Among the 263 HIV-positive patients, 237 (90.11%) were included in the final analysis. The overall prevalence of anemia was 26.2%. Factors that were significantly associated with anemia were past opportunistic infections, patients being in WHO clinical stage III and IV, and a BMI <18.5. Conversely, those patients who took anti-TB medication were less likely to have anemia. Conclusion . Our study shows that the severity of anemia among HIV/AIDS patients that had undergone ART is lower than most studies conducted in Ethiopia. We also found that opportunistic infection, WHO clinical staging, anti-TB treatment, and low BMI were significantly associated with anemia. Therefore, routine screening of patient nutritional status and opportunistic infections may be useful in predicting and controlling anemia in HIV/AIDS patients.